Library communication (Confluenţe Bibliologice, 2025)
The author describes the process of eﬀective communication in libraries, requirements for interpersonal communication with colleagues and students. The partnership between users and librarians is provided by the Director of the library, to determine them to understand each other, to act together, to communicate permanently.
Keywords: interpersonal communication; library staff; library users